Fire resistance of austenitic stainless steel beams with rectangular hollow sections - Lopes, Nuno (2022)
This paper presents a study on the structural behaviour of stainless steel profiles under fire conditions. An experimental campaign of three-point bending tests on rectangular hollow section beams of the grade 1.4301 (also known as 304) were conducted, considering both steady-state and transient state conditions. Prior to those tests, the mechanical characterization of the stainless steel was investigated. The constitutive laws obtained by tensile tests at high temperatures are compared with those recommended in Eurocode 3, whose respective material models were recently proposed for modifications, still requiring complete validation. In addition, numerical modelling of the bending tests has been performed afterwards achieving close approximation to the observed experimental results. Finally, analytical methods to predict the load-deflection behaviour are also presented. Good agreement between the considered methodologies was attained validating their application on the prediction of the fire behaviour of stainless steel beams.